Espécies de uso medicinal popular nativas e introduzidas cultivadas em cinco municípios do estado do amazonas - Freitas Hidalgo, Ari de [UNESP] (My University, 2002)
The objective if this work was a survey of medicinal plants plus commonly cultivated in quintais in Amazon State, Brazil. The work was carried out in five counties at the Solimões/Amazonas and Negro Rivers, by questionnaires, interviews and collections of botanical materials, using the literature to define the geographic origins. It was showed 105 species of medicinal plants, with average of 13 per house. The Amazonian plants, in general wood plants, meaning 10,9 percent of the total of species that was survey, with predominance of the American continent plants out of Amazonian (38,2 per cent). The major group was herbaceous or shrubs exotic plants, aromatics. In general, the peoples unknown the origin of the species of medicinal plants that use day after day.
Native and introduced species of folk medicinal plants cultivated in five counties of Amazon state - Brazil
Keywords: Amazonas and Negro rivers; Ethnobotany; Folk medicine; Geographic origin